Consumption of strawberries on a daily basis increases the non-urate 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical scavenging activity of fasting plasma in healthy subjects - Prymont-Przyminska, Anna; Zwolinska, Anna; Sarniak, Agata; Wlodarczyk, Anna; Krol, Maciej; Nowak, Michal; Graft-Johnson, Jeffrey de; Padula, Gianluca; Bialasiewicz, Piotr; Markowski, Jaroslaw; Rutkowski, Krzysztof P.; Nowak, Dariusz (Journal of Clinical Biochemistry and Nutrition, 2014)
Strawberries contain anthocyanins and ellagitanins which have antioxidant properties. We determined whether the consumption of strawberries increase the plasma antioxidant activity measured as the ability to decompose 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) in healthy subjects. The study involved 10 volunteers (age 41 ± 6 years, body weight 74.4 ± 12.7 kg) that consumed 500 g of strawberries daily for 9 days and 7 matched controls. Fasting plasma and spot morning urine samples were collected at baseline, during fruit consumption and after a 6 day wash-out period. DPPH decomposition was measured in both deproteinized native plasma specimens and pretreated with uricase (non-urate plasma). Twelve phenolics were determined with HPLC. Strawberries had no effect on the antioxidant activity of native plasma and circulating phenolics. Non-urate plasma DPPH decomposition increased from 5.7 ± 0.6% to 6.6 ± 0.6%, 6.5 ± 1.0% and 6.3 ± 1.4% after 3, 6 and 9 days of supplementation, respectively. The wash-out period reversed this activity back to 5.7 ± 0.8% (p<0.01). Control subjects did not reveal any changes of plasma antioxidant activity. Significant increase in urinary urolithin A and 4-hydroxyhippuric (by 8.7- and 5.9-times after 6 days of supplementation with fruits) was noted. Strawberry consumption can increase the non-urate plasma antioxidant activity which, in turn, may decrease the risk of systemic oxidants overactivity.